Triglyceride-glucose index is associated with symptomatic coronary artery disease in patients in secondary care - Alessandra da Silva; Ana Paula Silva Caldas; Helen Hermana Miranda Hermsdorff; Ângela Cristine Bersch-Ferreira; Camila Ragne Torreglosa; Bernardete Weber; Josefina Bressan (Cardiovascular Diabetology, 2019)
Abstract Background The triglyceride-glucose index (TyG index) is a tool for insulin resistance evaluation, however, little is known about its association with coronary artery disease (CAD), which is the major cardiovascular death cause, and what factors may be associated with TyG index. Objective To evaluate the association between the TyG index and the prevalence of CAD phases, as well as cardiovascular risk factors. Methods The baseline data of patients in secondary care in cardiology from Brazilian Cardioprotective Nutritional Program Trial (BALANCE Program Trial) were analyzed. Anthropometric, clinical, socio-demographic and food consumption data were collected by trained professionals. The TyG index was calculated by the formula: Ln (fasting triglycerides (mg/dl) × fasting blood glucose (mg/dl)/2) and regression models were used to evaluate the associations. Results We evaluated 2330 patients, which the majority was male (58.1%) and elderly (62.1%). The prevalence of symptomatic CAD was 1.16 times higher in patients classified in the last tertile of the TyG index (9.9 ± 0.5) compared to those in the first tertile (8.3 ± 0.3). Cardiometabolic risk factors were associated with TyG index, with the highlight for higher carbohydrate and lower lipid consumption in relation to recommendations that reduced the chance of being in the last TyG index tertile. Conclusion The TyG index was positively associated with a higher prevalence of symptomatic CAD, with metabolic and behavioral risk factors, and could be used as a marker for atherosclerosis. Trial registration ClinicalTrials.gov identifier: NCT01620398. Registered 15 June, 2012